2007
DOI: 10.1074/jbc.m609567200
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Insulin-like Growth Factor-binding Protein-2 in Human Glioblastoma Cells Reduces Both Invasiveness and Expression of Progression-associated Gene CD24

Abstract: Glioblastoma multiforme (GBM) is a malignant brain tumor characterized by rapid growth and extensive invasiveness. Overexpression of insulin-like growth factor-binding protein-2 (IGFBP-2) has been reported in GBM. However, it remains to be determined how IGFBP-2 is involved in the progression of GBM. We utilized short hairpin-RNA (shRNA) expression retroviral vectors to inactivate the IGFBP-2 gene permanently in two human GBM cell lines, U251 and YKG-1. The stable knockdown of IGFBP-2 resulted in decreased inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 40 publications
4
61
0
Order By: Relevance
“…Total RNAs were extracted with the Trizol reagent (Life Technologies), followed by DNase I (Roche Applied Science) treatment and phenolchloroform-isoamylalcohol extraction. For reverse transcription-PCR (RT-PCR), 3 Ag of total RNA were reverse transcribed with a mixture of oligo(dT) and random primer and processed for each PCR reaction as described previously (23). The PCR products were analyzed by 1.5% agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNAs were extracted with the Trizol reagent (Life Technologies), followed by DNase I (Roche Applied Science) treatment and phenolchloroform-isoamylalcohol extraction. For reverse transcription-PCR (RT-PCR), 3 Ag of total RNA were reverse transcribed with a mixture of oligo(dT) and random primer and processed for each PCR reaction as described previously (23). The PCR products were analyzed by 1.5% agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Knockdown of HAI-1/SPINT1. The knockdown vector was constructed by using a short hairpin RNA (shRNA) expression retroviral vector pSINsihU6 (TAKARA Bio) as described previously (23). The target sequence of HAI-1/SPINT1 gene was 5 ¶-GGGCAGGCATAGACTTGAAGG and scramble is 5 ¶-GGGACGGAGATTTCACGAGGA.…”
Section: Methodsmentioning
confidence: 99%
“…27 Cells were plated at 7 ϫ 10 5 per well in 60-mm dishes and transfected in triplicate by using the FuGENE 6 Transfection Reagent according to the manufacturer's protocol (Roche Diagnostics, Inc., Indianapolis, IN). We established stable cell lines COR-L105, NCI-H522, and HOP62 overexpressing IGFBP-2 after 4 weeks of selection in 400 g/ml of neomycin.…”
Section: Transient and Stable Transfectionsmentioning
confidence: 99%
“…22 Previous studies have shown that increased IGFBP-2 expression in a tumor promotes glioma cell migration and invasion through activation of the matrix metalloproteinase 2 protein and integrin pathway [23][24][25][26][27] and that this increased expression is associated with glioma malignancy and poor survival of glioma patients. 12,13,16,18,[28][29][30][31][32][33] Attenuation of IGFBP-2 by the tumor suppressor protein IIp45 or using small interfering RNA resulted in decreased cell motility and invasion.…”
mentioning
confidence: 99%
“…12,13,16,18,[28][29][30][31][32][33] Attenuation of IGFBP-2 by the tumor suppressor protein IIp45 or using small interfering RNA resulted in decreased cell motility and invasion. 23,26 Recently, IGFBP-2 has been found to be a "driver" oncogene for glioma development and progression. 28 IGFBP-2 overexpression has been linked to PTEN (phosphatase and tensin homolog) deletion and results in Akt activation.…”
mentioning
confidence: 99%